No prominent role for complement C1-esterase inhibitor in Marfan syndrome mice. (30th November 2022) - Hibender, Stijntje; Li, Siyu; Postma, Alex V; Hoogeland, Myrthe E; Klaver, Denise; Pouw, Richard B; Niessen, Hans W; Driessen, Antoine HG; Koolbergen, David R; de Vries, Carlie JM; Baars, Marieke JH; Houweling, Arjan C; et al.
Abstract : Marfan syndrome (MFS) is a connective tissue disorder causing aortic aneurysm formation. Currently, only prophylactic aortic surgery and blood pressure-lowering drugs are available to reduce the risk of aortic rupture. Upon whole genome sequencing of a Marfan family, we identified a complement gene C1R variant (p.Ser152Leu), which is associated with severe aortic patients. Therefore, we assessed the role of complement activation in MFS aortic tissue. Expression of various complement genes and proteins was detected in human and murine MFS aneurysm tissue, which prompted us to study complement inhibition in MFS mice. Treatment of the Fbn1 C1041G/+ MFS mice with human plasma-derived C1-esterase inhibitor Cetor® resulted in reduced complement deposition, decreased macrophage influx in the aorta, and lower circulating TNFα levels. However, in line with previous anti-inflammatory treatments, complement inhibition did not change the aortic dilatation rate in this MFS mouse model. Thus, while complement factors/component 3 activation were detected in human/murine MFS aorta, Cetor® had no effect on aortic dilatation in MFS mice, indicating that complement inhibition is not a suitable treatment strategy in MFS.